2022
DOI: 10.12928/pharmaciana.v12i1.21218
|View full text |Cite
|
Sign up to set email alerts
|

Anredera cordifolia leaves extract accelerates the wound healing of normal and hyperglycemic rats

Abstract: Anredera cordifolia ((Madeira vein (English) or Binahong (Indonesia language)) leaves contain ingredients that promote wound healing. This study aims to determine the effect of Madeira vein leaves ethanolic extract (MLE) on normal and hyperglycemic rat wounds. This is an experimental study using male Wistar rats aged 2-3 months, body weight between 250-300 grams induced by a single injection of streptozotocin dose 60 mg/kg BW intraperitoneally. Rats were divided into 8 groups namely normal without MLE, normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Binahong can be boiled for internal treatment, and the resulting infusion can be consumed. Research by Situmorang et al [33] suggests that the most effective concentration for rapid wound healing is 10% w/v. However, Pebri et al [34] found that higher concentrations of Binahong leaf extract, specifically 15%, expedited wound healing in incision wounds in mice more effectively than concentrations of 10% and 5%.…”
Section: Wound Healermentioning
confidence: 99%
“…Binahong can be boiled for internal treatment, and the resulting infusion can be consumed. Research by Situmorang et al [33] suggests that the most effective concentration for rapid wound healing is 10% w/v. However, Pebri et al [34] found that higher concentrations of Binahong leaf extract, specifically 15%, expedited wound healing in incision wounds in mice more effectively than concentrations of 10% and 5%.…”
Section: Wound Healermentioning
confidence: 99%